2018
DOI: 10.1177/2050640617742485
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of colorectal polyps for predicting residual or recurring adenoma using the Size/Morphology/Site/Access score

Abstract: Background and Aims: Endoscopic mucosal resection is an effective and safe procedure to manage large non-pedunculated colonic polyps for which residual/recurrent adenoma is the main drawback. Size/Morphology/Site/Access score determines polypectomy difficulty. We aimed to describe residual/recurrent adenoma rate according to Size/Morphology/Site/Access and to select the ize/Morphology/Site/Access cut-off to predict low residual/recurrent adenoma. Methods: This was a retrospective cohort study of endoscopic muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…This study demonstrated that the local colon adenoma recurrence rate in our cohort of patients with ≥ 20-mm colon LSTs managed using cap-fitted colonoscopy with EMR and ablation of the resection edge with APC was low (4.5 %). This adenoma recurrence rate was much lower than 16.0 % to 32 % reported in the literature on traditional EMR for non-pedunculated polyps (▶ Table 3) [3,10,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 83%
“…This study demonstrated that the local colon adenoma recurrence rate in our cohort of patients with ≥ 20-mm colon LSTs managed using cap-fitted colonoscopy with EMR and ablation of the resection edge with APC was low (4.5 %). This adenoma recurrence rate was much lower than 16.0 % to 32 % reported in the literature on traditional EMR for non-pedunculated polyps (▶ Table 3) [3,10,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 83%
“…An attempt to integrate various features of the polyp and technique has resulted in use of the SMSA score to identify lesions that are prone to recur after EMR [116,157,158]. Another score (the SERT-Sydney EMR recurrence tool), based on size (≥ 40 mm), IPB, and the presence of high grade dysplasia, was shown to predict recurrence at follow-up and could be used to stratify surveillance intervals, with those without risk factors undergoing first surveillance at 18 months, and those at risk following the standard protocol of first surveillance at 6 months [151].…”
Section: Recommendationmentioning
confidence: 99%
“…There are two scores that deal with technical difficulty or prediction of recurrence after endoscopic mucosal resection (EMR) of colorectal polyps [186][187][188][189][190][191][192]. The first score, called the SMSA score, is based on the variables size (S), morphology (M), site (S), and access (A), and has been studied by various groups, who have demonstrated the link between the SMSA score and the outcome of colonic EMR [187][188][189][190]. The second score, the Sydney EMR Recurrence Tool (SERT), has been shown to predict post-EMR recurrence [191].…”
Section: Hepatopancreaticobiliary Endoscopy -Ercpmentioning
confidence: 99%